2017
DOI: 10.3138/jvme.1215-193r
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Graduate Communication Skills in Professional Veterinary Practice

Abstract: Good communication skills are an important entry-level attribute of graduates of professional degrees. The inclusion of communication training within the curriculum can be problematic, particularly in programs with a high content load, such as veterinary science. This study examined the differences between the perceptions of students and qualified veterinarians with regards to the entry-level communication skills required of new graduates in clinical practice. Surveys were distributed to students in each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 84 publications
2
27
0
1
Order By: Relevance
“…Despite the importance of maintaining effective communication and sufficient information exchange for different stakeholders throughout the diagnosis and treatment of animals, there is a lack of appropriate measures to tackle issues in these matters. The review supports the findings of [15,18], and shows that systematic communication education is absent in the existing veterinary curriculum. Although studies such as McDermott's [13] and Jackson's [7] have explored the possible future approaches, it is obvious that the current curriculum is not yet well developed and adequate, likely resulting in communication challenges for veterinarians in their practice.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Despite the importance of maintaining effective communication and sufficient information exchange for different stakeholders throughout the diagnosis and treatment of animals, there is a lack of appropriate measures to tackle issues in these matters. The review supports the findings of [15,18], and shows that systematic communication education is absent in the existing veterinary curriculum. Although studies such as McDermott's [13] and Jackson's [7] have explored the possible future approaches, it is obvious that the current curriculum is not yet well developed and adequate, likely resulting in communication challenges for veterinarians in their practice.…”
Section: Discussionsupporting
confidence: 73%
“…Researchers have suggested that a systematic approach of teaching effective communication skills should be included in the veterinary education curriculum. The importance of communication skill education has been highlighted by Haldane et al [15], whose study indicates that both veterinary practitioners and students ranked verbal communication and interpersonal skills as the most vital abilities for potential veterinary practitioners hoping to join the industry. Moreover, in English speaking countries, the Calgary-Cambridge model is adopted in all veterinary institutions to strengthen the communication skills of the students and consequently improve the outcomes for clients [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many studies take gender into account when looking at these "professional skills in veterinarians". 20,21 Nevertheless, it has been reported that female veterinary students have higher expectations of themselves and feel they need to outperform by holding to stricter standards than men. 8,22,23 For example, Kogan et al 8 reported that female veterinary students scored significantly higher than men in those characteristics that defined a successful veterinary student.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary, however, to be able to obtain consent in a more truncated fashion in an emergency, where shared decision making may not be at the forefront of the process. Training in successful communication has received more attention in veterinary schools as of late, and is listed as highly sought after by veterinary employers (11).…”
Section: Surgery Performed For Underlying Problem Behaviorsmentioning
confidence: 99%